Neuroprotective effects of Apigenin on prenatal Valproic acid-induced autism spectrum disorder in rats - Mitra Farbin; Anahita Hejazi; Nahid Fakhraei; Yaser Azizi; Soraya Mehrabi; Razieh Hajisoltani (IBRO Neuroscience Reports)
Valproic acid (VPA) demonstrates teratogenic effects during pregnancy. Prenatal exposure to VPA may result in autism spectrum disorder (ASD) -like phenotypes. Apigenin, a natural flavonoid, has been shown to have neuroprotective impacts due to its antioxidant properties. This study aimed to investigate the protective effects of apigenin in prenatal Valproic acid-induced autism in rats. Female rats (220–240 g, 2–3 months) received a single dose of VPA (600 mg/kg, i.p.) on the 12.5th day of gestational. The male offspring were given oral apigenin (50 mg/kg, p.o.) or the vehicle for 30 days. Behavioral tests, biochemical assessments for oxidative stress markers and pro-inflammatory cytokines were performed. VPA-treated rats exhibited increased anxiety-like behavior, and repetitive behavior. Social interaction was reduced, and detection of the novel object was impaired. Also, VPA-treated rats have shown higher levels of oxidative stress malondialdehyde (MDA) and lower GPX and superoxide dismutase (SOD) levels. Furthermore, IL-6 and TNF-α increased in the prefrotalcortex decreased. On the other hand, apigenin-treated rats restored the cognitive consequences and lowered oxidative stress and inflammation in the prefrotalcortex. Conclusion: Chronic apigenin treatment restored the behavioral and biochemical abnormalities caused by prenatal VPA exposure.